Anode analysis and modelling hydrodynamic behaviour of the multiphase flow field in circular PEM water electrolyzer. (19th May 2023) - Ni, Aleksey; Upadhyay, Mukesh; Kumar, S. Shiva; Uwitonze, Hosanna; Lim, Hankwon
Abstract: A numerical study of the behaviour of the multiphase flow of an anode-porous transport layer of an aqueous electrolyzer with a proton-exchange membrane (PEM) of an aqueous electrolyzer is presented. A mixture model was used to study the flow behaviour in a circular-shaped anode box to determine the efficient design of a PEM water electrolyzer. As a result of the simulation, it was found that the model pressure drop profiles obtained by computational fluid dynamics (CFD) are in good agreement with the corresponding experimental data. In addition, the performance profile was predicted considering various PEM water electrolyzer cell improvement factors compared to the Bassline model. The results of the behaviour of two-phase flows with different velocity, pressure and volume fraction profiles, as well as with porous regions in the centre, are presented, which showed a key difference in the flow profile for various inlet and outlet flow configurations. In addition, the flow volume fraction behaviour was obtained at higher and lower water and oxygen rates. Three-dimensional (3D) modelling predicted flow characteristics for three different cell configurations. In this article, we also run simulations over a wide range of flow rates. The main results of the numerical study were discussed to shed light on the design of a high-performance PEM water electrolyzer. Highlights: 3D multiphase computational fluid dynamics (CFD) analysis of PEM water electrolyser. CFD model were verified with experiment data. Evaluate the different configuration profile with oxygen and water flow behavior. Key characteristics were discussed for optimum design of flow channel.